LINGUOPOETHIC CHARACTERISTICS OF NONVERBAL MEANS IN THE STORIES OF ISADJON SULTAN - Habibullayeva Sohibjamol Akmaljon qizi (Modern American Journals, 2025)
In this article, the paralinguistic tools as well as their types used in the stories of the writer Isajan Sultan, who had his own special place with his works in the current literary process, were subjected to analysis. The writer's poetic purpose for nonverbal media is concerned with issues such as their artistic aesthetic function as well as how adib describes paralinguistic tools that are difficult to express in words.
Keywords: Linguopoetics, nonverbal means, paralinguistics, language body, biological evolution, individual nonverbalism.